Biomedical engineering undergraduate education: A Canadian perspective. Issue 2 (April 2020) - Knowles, Nikolas K; DeCoito, Isha
Background: With an aging population and increasing demand on health care systems, biomedical engineering as an undergraduate program fits a growing societal need. As such, many Canadian universities have implemented biomedical engineering undergraduate programs. This provides a unique opportunity for core engineering faculty, engineering education researchers, and curriculum specialists to implement proven educational theories in the core curriculum of these programs to ensure exemplary and competent Canadian-trained biomedical engineering graduates. Purpose: This paper discusses the need for biomedical engineering as a core undergraduate program in Canada, the historical context of educational theories as related to biomedical undergraduate engineering education, a framework for the implementation of proven strategies, and learner-centric methods that benefit the learner, mentor, and society as a whole. Scope/method: The historical context of curriculum theories related to biomedical engineering undergraduate education, evaluation of the intrinsic and extrinsic curriculum theories in current biomedical engineering undergraduate education, educating progressive learners and development of future biomedical engineering undergraduate education curriculum, is explored. Conclusion: The integration of educational theories in the development of a biomedical engineering undergraduate engineering education is essential to ensure learners are provided with opportunities to experience cutting edge, quality engineering education. Empirical evidence demonstrates the successful implementation of applied methodologies such as model-electing activities, problem-based learning, and the flipped classroom. Providing biomedical engineering faculty with professional development opportunities around the successfully implementation of these tools aimed at culturally diverse, globalized 21st-century learners, can be catalytic in shifting to a new paradigm for engineering education in Canada and globally.